LOCKE’S NATURAL RIGHTS AND ISLAMIC RIGHTS: LIFE, LIBERTY, PROPERTY, AND HUMAN DIGNITY IN THE LIGHT OF MAQASID AL-SHARIʿAH - Dr. Muhammad Afzal; Dr. Abdul Majid; Muhammad Harris Suhaib (Policy Journal of Social Science Review, 2026)
This article compares John Locke’s theory of natural rights with the Islamic framework of rights and protections, particularly through the maqasid al-shariʿah. Locke identifies life, liberty, and property as fundamental interests that government must protect. Islamic law similarly protects life, religion, intellect, family or lineage, and property, while grounding these protections in revelation, moral duty, justice, and human dignity. This article argues that Islamic rights should not be understood as merely abstract moral ideals, nor as rules that appeared only in later legal writing. Although the formal classification of maqasid was systematized by scholars such as al-Ghazali centuries later, its underlying protections were rooted in the Qur’an, the Sunnah, and the legal-social practices of the Medinan community. Using a qualitative comparative method, the study examines Locke’s Second Treatise of Government, Qur’anic provisions, selected Hadith, Seerah literature, and modern maqasid scholarship. The findings show substantial overlap between Locke and Islam regarding the protection of life, freedom from arbitrary domination, and property. However, the Islamic framework is broader, as it also protects religion, intellect, family, honor, and social welfare. The article concludes that, by the criterion of comprehensiveness and the integration of rights with duties, the maqasid framework is more coherent. This conclusion is normative and does not deny Locke’s major contribution to limiting tyranny and defending individual freedom. Keywords: John Locke; natural rights; maqasid al-shariʿah; life; liberty; property; human dignity; Islamic law; human rights.